Effect of normal pressure on the critical compressive and shear stress of curved sheet - Rafel, Norman (National Advisory Committee for Aeronautics, 1945)
Results are presented of tests of two sets of 20 curved-sheet specimens to determine the effect of normal pressure on the critical compressive and shear stress of curved sheet. It was found that normal pressure raised the critical compressive and shear stress of curved sheet except when outward bulging occurred in compression, in which case the critical stress was lowered by normal pressure.
NACA Wartime Report L-57.
Originally issued as NACA as Advance Restricted Report L5B10 (March 1945).
Prepared at the Langley Memorial Aeronautical Laboratory, Langley Field, Virginia.
Keywords: Box beams.; Aluminum alloys.; Plates (Engineering) -- Curvature.; Loads (Mechanics); Shear (Mechanics); Buckling (Mechanics); Strains and stresses.; Charts, diagrams, etc.; elektronické knihy; electronic books